PECULIARITIES OF FOLLICLE GROWTH REGULATION IN ASSISTED REPRODUCTIVE TECHNOLOGY PROGRAMS IN WOMEN WITH A “POOR” OVARIAN RESPONSE - Джалилова, Эльмира Рафиковна; Башмакова, Надежда Васильевна; Чистякова, Гузель Нуховна; Газиева, Ирина Александровна (Mother and Baby in Kuzbass, 2024)
Poor ovarian response depends, among other factors, on the biochemical composition of the follicle microenvironment. Modern studies emphasize the relationship between the content of vascular tone regulators and angiogenesis, oxidative stress and the quality of mature oocytes, however, there is no unified theory in the literature determining the effect of vascular tone regulators and angiogenic factors on ovogenesis and folliculogenesis, and their role in the pathogenesis of the "poor" ovarian response. Objective – to evaluate the content of vascular tone and angiogenesis regulators in follicular fluid in patients with a «poor» ovarian response to stimulation in IVF programs. Materials and Methods. 56 women, depending on the ovarian response to stimulation in the IVF program, were divided into two groups – with a «poor» and a normal response, samples of follicular fluid (FF) of preovulatory follicles (d = 16-20 mm) were taken. Depending on the presence of the oocyte-cumulus complex (OCC) inside the follicle, the patients from the FIGHT were assigned to different subgroups. In patients with a normal response, OCS were found in all FF samples. The content of endogenous nitrite (NO2) and nitrate (NO3), vascular endothelial growth factor (VEGF-A) and the concentration of soluble receptor (sVEGFR2) in the follicular fluid of the patients were determined. Results. The absence of OCC in patients with a «poor» response correlates with a low content of VEGF-A and sVEGFR2 in FF. The level of endogenous NO2 was statistically significantly increased in FF much without the oocyte-cumulus complex as compared with FF with OCC. Conclusions. An increase in the production of NO2 in FF without OCC probably indicates the possibility of follicular angiogenesis and subsequent growth, however, the processes of vascularization are limited by insufficient volumes of vascular endothelial growth factor and its receptor. As a result, the blood supply to the follicle is disrupted and the supply of substances necessary for the formation of high-quality OCC slows down.